Childhood maltreatment and amygdala connectivity in methamphetamine dependence: a pilot study. Issue 6 (29th September 2014) - Dean, Andy C.; Kohno, Milky; Hellemann, Gerhard; London, Edythe D.
Abstract Introduction Childhood maltreatment, a well‐known risk factor for the development of substance abuse disorders, is associated with functional and structural abnormalities in the adult brain, particularly in the limbic system. However, almost no research has examined the relationship between childhood maltreatment and brain function in individuals with drug abuse disorders. Methods We conducted a pilot study of the relationship between childhood maltreatment (evaluated with the Childhood Trauma Questionnaire; Bernstein and Fink 1998) and resting‐state functional connectivity of the amygdala (bilateral region of interest) with functional magnetic resonance imaging in 15 abstinent, methamphetamine‐dependent research participants. Within regions that showed connectivity with the amygdala as a function of maltreatment, we also evaluated whether amygdala connectivity was associated positively with negative affect and negatively with healthy emotional processing. Results The results indicated that childhood maltreatment was positively associated with resting‐state connectivity between the amygdala and right hippocampus, right parahippocampal gyrus, right inferior temporal gyrus, right orbitofrontal cortex, cerebellum, and brainstem. Furthermore, connectivity between the amygdala and hippocampus was positively related to measures of depression, trait anxiety, and emotion dysregulation, and negatively related to self‐compassion and dispositional mindfulness. Conclusions These findings suggest that childhood maltreatment may contribute to increased limbic connectivity and maladaptive emotional processing in methamphetamine‐dependent adults, and that healthy emotion regulation strategies may serve as a therapeutic target to ameliorate the associated behavioral phenotype. Childhood maltreatment warrants further investigation as a potentially important etiological factor in the neurobiology and treatment of substance use disorders.